Synthesis and Characterization of TiO2 from Lampung’s Iron Sand using Leaching Method with Temperature Variation: Iqbal Firdaus, Anggi Stevani, Yudhistira Novita Handayani, Nadia Febriyanti, Roniyus Marjunus, Posman Manurung - Iqbal Firdaus Iqbal Firdaus; Anggi Stevan Anggi Stevan; Yudhistira Novita Handayani Yudhistira Novita Handayani; Nadia Febriyanti Nadia Febriyanti; Roniyus Marjunus Roniyus Marjunus; Posman Manurung Posman Manurung (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2021)
Ilmenite is a natural material in the form of sand which contains heavy metal minerals that are very abundant in Lampung province. This research aims to determine the content of TiO2 from Lampungs iron sand by leaching method with temperature variation. The iron sand are mixed with sodium hydrogen carbonate (NaHCO3), then heated at 7000 C for an hour. This research uses 5 samples with leaching temperature variation of 70, 80, 90, 100, and 1100 C for 2 hours. The acid leaching process uses HCl 12 M with a ratio of iron sand and HCl of 1:4, while the water leaching process uses 50 ml of distilled water. Furthermore, the samples are characterized using XRD and XRF to determine TiO2 content in the iron sand. The result shows that the highest amount of TiO2 is obtained in the sample with the leaching temperature of 1100 C for 2 hours, which is approximately 61%.